PENGARUH DISIPLIN KERJA, ETOS KERJA, PRODUKTIVITAS KERJA TERHADAP PRESTASI KERJA PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA METRO - Ayuningsih, Tika; Suwarto, Suwarto (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The background of this study is work performance which is an achievement achieved. The purpose of this research is to determine the ef ect of work discipline, work ethic and work productivity af ect work performance. In this research using primary data collected by descriptive survey method and sampling techniques in the form of census sampling and saturated sampling of 60 people. Respondents of the Regional Tax and Retribution Management, Of ice of Metro City. Testing the instrument requirements used include validity and reliability, normality test, homogeneity test, linearity test and regression significance as testing the requirements for multiple linear regression analysis. Based on the results of research using multiple linear regression analysis obtained work, discipline does not influence work performance, work ethic has an ef ect on work performance and productivity does not af ect employee performance.